IMPLEMENTATION OF BUREAUCRACY REFORM THROUGH IMPLEMENTATION OF APPARATUS HUMAN RESOURCES MANAGEMENT TOWARDS SOCIETY BUREAUCRACY 5.0 - Romdana . (Institut Pendidikan Tapanuli Selatan, 2022)
The utilization of technology in dealing with various problems in the noble public sector is carried out through society 5.0. This causes the need for multiple changes in the bureaucracy to run following society 5.0. Therefore, the researcher intends to examine the implementation of bureaucratic reform towards society 5.0 through the management of human resources of the Apparatus.The research was carried out using a qualitative approach with secondary data sources. The study results indicate that various problems occur in carrying out reforms, such as a culture of corruption, bureaucratic pathology, to the unprepared use of technology in the bureaucracy for public services. This causes the importance of bureaucratic reform that is carried out correctly to deal with various problems that will continue to emerge.